2011
DOI: 10.2190/ag.72.4.c
|View full text |Cite
|
Sign up to set email alerts
|

The Relationship between Age, Gender, Historical Change, and Adults' Perceptions of Mental Health and Mental Health Services

Abstract: The purpose of this study was to explore the impact of age, historical change, and gender on perceptions of mental health and mental health services. Using multidimensional measures to assess such perceptions among older adults (1977, 1991, 2000), and younger adults (1991, 2000), we expected that older adults would have less positive mental health perceptions than would younger adults, that more recently born cohorts of older persons would evidence more positive perceptions, and that women, especially those mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
14
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(17 citation statements)
references
References 39 publications
1
14
0
Order By: Relevance
“…Accordingly, we did not attempt to make samples representative of larger populations, because the studies were not intended to make broad statements or generalizations about tolerance within these groups. There are many studies that have investigated tolerance in different populations (e.g., Diefenbach & West, 2007;Hayes et al, 2004), including the mental health professions (e.g., Lauber, Anthony, Ajdacic-Gross, & Rössler, 2004;Sadow, Ryder, & Webster, 2002;Smith & Cashwell, 2010;Theriot & Lodato, 2012), that have linked tolerance to different individual demographic variables (e.g., Anglin, Link, & Phelan, 2006;Currin, Hayslip, & Temple, 2011;Hinkelman & Granello, 2003) or that have measured the effects of education or training on tolerance (e.g., Krameddine, DeMarco, Hassel, & Silverstone, 2013;Linden & Kavanagh, 2012;Pande, Saini, & Chaudhury, 2011). In the current series of studies, we conducted within-sample comparisons to determine whether, regardless of overall levels of tolerance within each sample, there were significant effects of premodified or postmodified language on tolerance.…”
Section: Discussionmentioning
confidence: 99%
“…Accordingly, we did not attempt to make samples representative of larger populations, because the studies were not intended to make broad statements or generalizations about tolerance within these groups. There are many studies that have investigated tolerance in different populations (e.g., Diefenbach & West, 2007;Hayes et al, 2004), including the mental health professions (e.g., Lauber, Anthony, Ajdacic-Gross, & Rössler, 2004;Sadow, Ryder, & Webster, 2002;Smith & Cashwell, 2010;Theriot & Lodato, 2012), that have linked tolerance to different individual demographic variables (e.g., Anglin, Link, & Phelan, 2006;Currin, Hayslip, & Temple, 2011;Hinkelman & Granello, 2003) or that have measured the effects of education or training on tolerance (e.g., Krameddine, DeMarco, Hassel, & Silverstone, 2013;Linden & Kavanagh, 2012;Pande, Saini, & Chaudhury, 2011). In the current series of studies, we conducted within-sample comparisons to determine whether, regardless of overall levels of tolerance within each sample, there were significant effects of premodified or postmodified language on tolerance.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, ethnic minority group members, almost all of whom were African American, were more likely to prefer to see a counselor than Caucasians. In prior research with the general population, age has shown mixed relationships with attitudes toward mental health services [37,38], and African Americans have shown more positive attitudes toward mental health services than Caucasians, despite their lower rates of service use [21,39]. In our study, rates of mental health service use before and after the lung cancer diagnosis did not significantly differ between ethnic minorities and Caucasians (data not shown); thus, prior experience with mental health services does not account for the findings.…”
Section: Discussionmentioning
confidence: 99%
“…Interesting changes in attitudes toward seeking mental health services over time were observed by Currin et al [15] in their study carried out on groups of older and younger adults in 1977, 1991 and 2001. The results were rather ambiguous as they found increasingly positive attitudes among the older group from 1977 to 1991, and both the older and younger participants demonstrated more negative help-seeking attitudes from 1991 to 2001.…”
Section: Introductionmentioning
confidence: 98%